PENGARUH LITERASI KEUANGAN TERHADAP KEPUTUSAN INVESTASI YANG DIMEDIASI OLEH PENGALAMAN INVESTASI PADA KOMUNITAS INVESTOR DI KOTA MALANG - Ferdiansyah, Rifaldy; Kustiandi, Januar (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2025)
This study examines the effect of financial literacy on investment decisions mediated by investment experience within the investor community in Malang City. Financial literacy helps young investors make rational decisions, while investment experience enhances their ability to assess opportunities and risks. A quantitative approach was used with Structural Equation Modeling (SEM) analysis through SmartPLS. The research population consists of 626 individuals who are part of the investor community in five leading universities in Malang City. A sample of 261 respondents was selected using the Slovin formula to obtain a representative sample. The results show that financial literacy and investment experience significantly influence investment decisions, with investment experience also affecting decisions through financial literacy as a mediator. This study contributes to understanding how financial literacy strengthens the positive impact of investment experience, ultimately leading to wiser investment decisions. The findings are expected to support the development of more effective financial literacy education policies for the younger generation. Keywords: financial literacy, investment decisions, investment experience, investor community, SmartPLS